2022
DOI: 10.33087/jiubj.v22i3.2554
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perilaku Pengelolaan Keuangan terhadap Penerima Kartu Indonesia Pintar pada Mahasiswa UPN ”Veteran” Jawa Timur

Abstract: Students as the young generation must understand managing finances wisely as a prosperous financial growth and development in the present and in the future. Financial management behavior as a measure of student success in dealing with their finances. This study aims to determine the effect of financial knowledge, financial attitude, and locus of control on financial management behavior. The population for this study were students who received the Indonesian Smart College Card (KIP-K) UPN "Veteran" East Java. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…According to the Planned Theory of conduct, a person's conduct when utilizing paylater is determined by their locus of control, which is a function of their perceived behavioral control. This is consistent with study by Mariana et al (2022) and Fadilah & Purwanto (2022), which found that better financial behavior is correlated with a stronger locus of control.…”
Section: The Effect Of Locus Of Control (X2) On Financial Behavior (Y)supporting
confidence: 92%
See 2 more Smart Citations
“…According to the Planned Theory of conduct, a person's conduct when utilizing paylater is determined by their locus of control, which is a function of their perceived behavioral control. This is consistent with study by Mariana et al (2022) and Fadilah & Purwanto (2022), which found that better financial behavior is correlated with a stronger locus of control.…”
Section: The Effect Of Locus Of Control (X2) On Financial Behavior (Y)supporting
confidence: 92%
“…Locus of control can be defined as an individual's self-control over their future, enabling them to prioritize needs over desires, as described by Pratiwi et al in 2021. According to Rotter in (Dewanti & Asandimitra, 2021) someone has a good locus of control, it is expected that they will have a view of the future so that they will prioritise their needs over their desires. Locus of control has a positive impact on financial behavior, therefore the greater the locus of control, the better the person's financial behavior, according to research by Mariana et al in 2022. Financial behavior is impacted by an individual's locus of control, as it fosters increased self-awareness, responsibility, and decision-making in financial matters, as suggested by Fadilah and Purwanto in 2022. According to the Theory of Planned Behavior (TPB), personal intention is a factor that exerts control over a person's willingness to engage in certain events or actions.…”
Section: Locus Of Controlmentioning
confidence: 99%
See 1 more Smart Citation